HIV-1 Vif can directly inhibit apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3G-mediated cytidine deamination by using a single amino acid interaction and without protein degradation - Santa-Marta, M (2015)
The human apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3G (APOBEC3G), also known as CEM-15, is a host-cell factor involved in innate resistance to retroviral infection. HIV-1 viral infectivity factor (Vif) protein was shown to protect t